THE REALITY OF PRACTICING SERVANT LEADERSHIP DIMENSIONS FOR HEADS OF SCIENTIFIC DEPARTMENTS IN BAGHDAD UNIVERSITIES FROM THE POINT OF VIEW OF THE FACULTY MEMBERS OF THE FACULTIES OF PHYSICAL EDUCATION AND SPORTS SCIENCES (ResearchJet Journal of Analysis and Inventions, 2022)
Universities undertake multiple and important responsibilities and tasks in the field of preparing specialized competencies to take on the burdens. Development in different areas of life, and in the field of finding scientific solutions to the problems faced by society, in addition to Their role is to spread and develop knowledge of the various branches of science, and therefore universities are a major means for the progress of society and an address its renaissance.